2004
DOI: 10.1097/01.olq.0000123652.88904.9b
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Remains the Principal Cause of Initial Anogenital Herpes in Edinburgh, Scotland

Abstract: HSV-1 remains the most common cause of symptomatic first-episode anogenital herpes, especially among young women in our clinic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
2
16
0
1
Order By: Relevance
“…Orogenital and oroanal practices were significant predictors of incident HSV-1 infection in univariate analysis, and insertive orogenital sex remained significant in the multivariate model. The increasing occurrence of orogenital sex has been suspected to be the reason for the increasingly common occurrence of HSV-1-related genital herpes [5,6,8,39], and our data provide longitudinal evidence to support this hypothesis. Another factor that was strongly suggestive of sexual transmission of HSV-1 was the markedly higher prevalence of HSV-1 infection in individuals 25-34 years of age (76%), compared with that in individuals !25 years of age (54%).…”
Section: Discussionsupporting
confidence: 80%
“…Orogenital and oroanal practices were significant predictors of incident HSV-1 infection in univariate analysis, and insertive orogenital sex remained significant in the multivariate model. The increasing occurrence of orogenital sex has been suspected to be the reason for the increasingly common occurrence of HSV-1-related genital herpes [5,6,8,39], and our data provide longitudinal evidence to support this hypothesis. Another factor that was strongly suggestive of sexual transmission of HSV-1 was the markedly higher prevalence of HSV-1 infection in individuals 25-34 years of age (76%), compared with that in individuals !25 years of age (54%).…”
Section: Discussionsupporting
confidence: 80%
“…For instance, a Swedish study (64) showed that 44% of 97 patients presenting with culture-positive primary genital herpes have HSV-1 infection, and that 64% of serologically confirmed primary genital herpes was attributable to HSV-1. In Edinburgh, Scotland (United Kingdom), HSV-1 accounted for 42% and 62% of virologically confirmed first episode genital herpes outbreaks in men and women, respectively (65). Among American college students, the proportion of newly diagnosed genital herpes attributed to HSV-1 rose dramatically from 31% in 1993 to 78% in 2001 (P<0.001; linear trend P<0.001) (66).…”
Section: Hsv-1 Accounts For An Increasing Burden Of Genital Herpesmentioning
confidence: 99%
“…Indeed, many studies have reported that HSV-1 may account for up to 80 % of cases of first-episode genital and anogenital herpes [12,[66][67][68][69][70][71][72][73]. Interestingly, a gradual transition from HSV-2 to HSV-1 as the leading causes of primary genital herpes can be observed in numerous recent studies [74][75][76].…”
Section: Incidence and Prevalence Of Hsv-2mentioning
confidence: 99%